2021
DOI: 10.3389/fpsyg.2021.631538
|View full text |Cite
|
Sign up to set email alerts
|

Snitches Get Stitches and End Up in Ditches: A Systematic Review of the Factors Associated With Whistleblowing Intentions

Abstract: Blowing the whistle on corruption or wrongdoing can facilitate the detection, investigation, and then prosecution of a violation that may have otherwise gone undetected. The purpose of this systematic review was to identify the factors that are associated with intentions to blow the whistle on wrongdoing. We searched Academic Search Premier, CINAHL Complete, Education Research Complete, ERIC, Medline, PsycARTICLES, PsycINFO, Regional Business News, and SPORTDiscus in January 2020. The quality of evidence was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 209 publications
(437 reference statements)
7
14
0
1
Order By: Relevance
“…It is also important to note that although an increased likelihood of reporting organizational dysfunctions is beneficial to the organization, it may well be detrimental to the individuals themselves if they are subject to retribution (see Nicholls et al, 2021 for a review of the research literature on consequences of whistleblowing). Future work should address what organizational systems need to be implemented in order to reap the benefit of autistic employees while shielding them from potential negative repercussions.…”
Section: Organizational Implicationsmentioning
confidence: 99%
“…It is also important to note that although an increased likelihood of reporting organizational dysfunctions is beneficial to the organization, it may well be detrimental to the individuals themselves if they are subject to retribution (see Nicholls et al, 2021 for a review of the research literature on consequences of whistleblowing). Future work should address what organizational systems need to be implemented in order to reap the benefit of autistic employees while shielding them from potential negative repercussions.…”
Section: Organizational Implicationsmentioning
confidence: 99%
“…Hence, in this study, exploratory analysis will be undertaken in relation to the potential influence of personality on bystander decision-making when witnessing IPV. Systematic reviews have also found a link between morality and whistleblowing (Nicholls et al, 2021). According to the moral foundations theory (Graham et al, 2009), individuals consider five moral values (harm, fairness, loyalty, authority and purity) when deciding whether a certain behaviour is right or wrong.…”
Section: Personal Factors Of the Whistleblowermentioning
confidence: 99%
“…Systematic reviews have found mixed findings in relation to gender and whistleblowing (Nicholls et al , 2021), with some studies finding females are more likely to report misconduct than males (Keil et al , 2010) and others finding the opposite effect (Cheng et al , 2015). This is likely due to the moderating effect of system variables and failing to consider the gender of the: whistleblower; wrong-doer; and victim.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations